The librarian of Boone's Hollow : a novel - Sawyer, Kim Vogel (WaterBrook, 2020)
"A traveling librarian ventures into the mining towns of Kentucky on horseback and rediscovers her passions in this powerful novel from the best-selling author of A Silken Thread"--